Evaluation of stacked resonators to enhance the performance of a surface receive-only array for prostate MRI at 3Tesla - Chacón-Caldera, Jorge; Malzacher, Matthias; Vetter, Yannik; Davids, Mathias; Schad, Lothar R. (Magnetic resonance imaging, 2018)
Prostate MRI is an important tool to diagnose and characterize cancer. High local sensitivity and good parallel imaging performance are of paramount importance for diagnostic quality and efficiency. The purpose of this work was to evaluate stacked resonators as part of a surface receiver array for prostate MRI at 3Tesla. A base array of 6-channels consisting of a flexible anterior and a rigid posterior part were built each with three loop coils. A pair of stacked resonators was added concentrically to the center loops (anterior and posterior) of the base array. The evaluated stacked resonators were butterflies, composites and dipoles which yielded a total of three 8-channel arrays. The arrays were compared using noise correlations and single-channel signal-to-noise ratio maps in a phantom. Combined signal-to-noise ratio maps and parallel imaging performances were measured and compared in vivo in 6 healthy volunteers. The results were compared to the base and a commercial array. The SNR values in the prostate yielded by all the arrays were not statistically different using fully sampled k-space. However, significant differences were found in the parallel imaging performance of the arrays. More specifically, up to 88% geometric factor reduction was found compared to the commercial array and up to 83% reduction compared to the base array using butterfly coils. Thus, signal-to-noise ratio improvements were observed with stacked resonators when using parallel imaging. The use of stacked elements, in particular butterfly coils, can improve the performance of a base array consisting solely of single loops when using parallel imaging. We expect prostate MRI at 3Tesla to benefit from using combinations of single loops and stacked resonators.
Available online 25 July 2018
Gesehen am 08.04.2019